Mekanisme Resistensi Insulin Terkait Obesitas - Rheza Paleva Agus (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Obesity is a condition where excess body fat accumulation occurs. This has become an increasingly progressive problem and the prevalence in Indonesia continues to increase every year. This pathological condition also triggers various metabolic and other non-metabolic disorders. Insulin resistance is one thing that underlies various diseases related to obesity. In obesity, adipocytes experience hypertrophy and will lose their physiological functions. The active products of these two products trigger an increase in the production of Nitric Oxide (NO) and the formation of peroxynitrite derivatives (ONOO), which in turn separates IRS-1 from the activation of PI3K and Akt which are key to translocation of glucose transporters (GLUT4) to the cell surface and activation of glucose transport in glucose myocytes, resulting in insulin resistance. Effective therapy that can be done in obesity is weight loss by doing routine physical activity that can indirectly prevent pathological conditions associated.